AUDIT SISTEM INFORMASI AKADEMIK MENGGUNAKAN METODE COBIT 5 - Tri Rahayu; Nurhafifah Matondang; Bayu Hananto (Jurnal Teknologi Informasi dan Pendidikan, 2020)
The purpose of this study is to measure the level of maturity and application of information technology performance in implementing the Academic Information System (SIAKAD) at the "Veteran" National Development University of Jakarta (UPNVJ) because they see that the current utilization has not been maximized in IT utilization in terms of planning, implementation and supervision. The method to measure the level of maturity using the COBIT 5 method and the results obtained focus on 5 domains, namely the Deliver, Service and Support process in IT UPNVJ located at level 3 with a value of 2.80 and has a gap of 1.20. Results in the Evaluate, Direct and Monitor, Align, plan and organize, Build, Aquire and implement, BAI04 and Monitor, Evaluate and Assess domains in IT UPNVJ have level 2 with a value of 2.00 and have a gap of 2.00 and the Capability Level results are based on the overall 5 process domains have a value of 2.20 and a gap of 1.80, based on the specified target level, capability level 4.00.